A Study on Mental Health, Psychological Support and Life Satisfaction For Tribal Community In Nilgiris-TN - Manikandan A.; Rithika S; Shahina.A (International Journal of Community Health Nursing And Practices, 2025)
This research investigates the mental health challenges, psychological support systems, and overall life satisfaction among tribal communities in the Nilgiris district of Tamil Nadu. These indigenous groups, including the Todas, Kotas, Irulas, and Kurumbas, are undergoing significant social transitions due to modernization, environmental change, and cultural shifts: factors that increasingly influence their mental well-being. The primary objectives of this study are to assess the prevalence of mental health issues such as anxiety and depression, evaluate the availability and effectiveness of psychological support systems, and identify key factors impacting life satisfaction within these communities. A quantitative research design was employed, using structured surveys administered to a sample of 60 participants drawn from various tribal groups. The data collected were analyzed using SPSS software, which helped in identifying statistical patterns, correlations, and critical influences on mental health outcomes. The findings indicate a high prevalence of mental health challenges, particularly feelings of sadness, moderate stress, and emotional exhaustion. Despite the presence of traditional support systems, formal psychological services remain largely inaccessible, leading many individuals to rely on familial, spiritual, and community-based practices. While these traditional methods offer some relief, they may not fully address the complexities of modern psychological distress. The study concludes with key recommendations, including the integration of traditional and modern mental health practices, improved access to culturally sensitive mental health services, and the development of community-driven interventions aimed at enhancing life satisfaction and holistic well-being among tribal populations in the Nilgiris.
Keywords: India